Crosslinking Induced Reassembly of Multiblock Polymers: Addressing the Dilemma of Stability and Responsivity. Issue 8 (6th March 2020) - Yang, Rui; Zheng, Yi; Shuai, Xiaoyu; Fan, Fan; He, Xueling; Ding, Mingming; Li, Jianshu; Tan, Hong; Fu, Qiang
Abstract: Physical or chemical crosslinking of polymeric micelles has emerged as a straightforward approach to overcome the intrinsic instability of assemblies. However, the crosslinking process may compromise the responsivity of nanosystems and result in inefficient release of payloads. To address this dilemma, a crosslinking induced reassembly (CIRA) strategy is reported here to simultaneously increase the kinetic and thermodynamic stability and redox‐responsivity of polymeric micelles. It is found that the click crosslinking of a model multiblock polyurethane at the micellar interface induces microphase separation between the soft and hard segments. The aggregation of hard domains gathers liable disulfide linkages around the interlayer of micelles, which could facilitate the attack of reducing agents and act as an intelligent on‐off switch for high stability and triggered release. As a result, the CIRA approach enables an enhanced tumor targeting, improved biodistribution and excellent therapeutic efficacy in vivo. This work provides a facile and versatile platform for controlled delivery applications. Abstract : Crosslinking induced reassembly (CIRA) of multiblock polyurethanes induces a microphase separation between the soft and hard segments and gathers liable disulfide linkages around the interlayer of micelles, thus leading to a simultaneous improvement of stability and responsivity of assemblies. The CIRA strategy enables an intelligent on‐off switch for enhanced tumor targeting, improved biodistribution and excellent therapeutic efficacy in vivo.